Efficacy of ketogenic diet on body composition during resistance training in trained men: a randomized controlled trial - Salvador Vargas; Ramón Romance; Jorge L. Petro; Diego A. Bonilla; Ismael Galancho; Sergio Espinar; Richard B. Kreider; Javier Benítez-Porres (Taylor & Francis Group, 2018)
Background Ketogenic diets (KD) have become a popular method of promoting weight loss. More recently, some have recommended that athletes adhere to ketogenic diets in order to optimize changes in body composition during training. This study evaluated the efficacy of an 8-week ketogenic diet (KD) during energy surplus and resistance training (RT) protocol on body composition in trained men. Methods Twenty-four healthy men (age 30 ± 4.7 years; weight 76.7 ± 8.2 kg; height 174.3 ± 19.7 cm) performed an 8-week RT program. Participants were randomly assigned to a KD group (n = 9), non-KD group (n = 10, NKD), and control group (n = 5, CG) in hyperenergetic condition. Body composition changes were measured by dual energy X-ray absorptiometry (DXA). Compliance with the ketosis state was monitored by measuring urinary ketones weekly. Data were analyzed using a univariate, multivariate and repeated measures general linear model (GLM) statistics. Results There was a significant reduction in fat mass (mean change, 95% CI; p-value; Cohen's d effect size [ES]; − 0.8 [− 1.6, − 0.1] kg; p < 0.05; ES = − 0.46) and visceral adipose tissue (− 96.5 [− 159.0, − 34.0] g; p < 0.05; ES = − 0.84), while no significant changes were observed in the NKD and CG in fat mass (− 0,5 [− 1.2, 0.3] kg; p > 0.05; ES = − 0.17 and − 0,5 [− 2.4, 1.3] kg; p > 0.05; ES = − 0.12, respectively) or visceral adipose tissue (− 33.8 [− 90.4, 22.8]; p > 0.5; ES = − 0.17 and 1.7 [− 133.3, 136.7]; p > 0.05; ES = 0.01, respectively). No significant increases were observed in total body weight (− 0.9 [− 2.3, 0.6]; p > 0.05; ES = [− 0.18]) and muscle mass (− 0.1 [− 1.1,1.0]; p > 0,05; ES = − 0.04) in the KD group, but the NKD group showed increases in these parameters (0.9 [0.3, 1.5] kg; p < 0.05; ES = 0.18 and (1.3[0.5, 2.2] kg; p < 0,05; ES = 0.31, respectively). There were no changes neither in total body weight nor lean body mass (0.3 [− 1.2, 1.9]; p > 0.05; ES = 0.05 and 0.8 [− 0.4, 2.1]; p > 0.05; ES = 0.26, respectively) in the CG. Conclusion Our results suggest that a KD might be an alternative dietary approach to decrease fat mass and visceral adipose tissue without decreasing lean body mass; however, it might not be useful to increase muscle mass during positive energy balance in men undergoing RT for 8 weeks.